Fenômeno de congruência e não congruência sobre a função exponencial em materiais didáticos - Ginez, Patricia Costa (Universidade Federal de São Carlos, 2020)
The students' lack of understanding concerning certain contents in Mathematics leads us to rethink teaching methodologies so as to enable strategies that favor learning, looking at the teaching materials that are used in this process. Thus, the objective of this study was to analyze how the mobilization and coordination of different records of semiotic representation of the exponential function in the supporting material of the São Paulo State Curriculum, the Teacher's Notebook and the textbook by Iezzi et al. (2016). Results of other researches pointed out difficulties on the part of the students in understanding the concept of function, in particular, the exponential function, as well as the way it is presented in the Teacher's Notebook. For this, our research was based on Raymond Duval's Theory on Semiotics Representations Registers, which discusses the importance of different semiotic representations in mathematical learning. The information that comprised the research was displayed in tables highlighting the records of departure representation and records of arrival representation for the analysis of transformations according to Raymond Duval's theory. The research answered the question: “How is the concept of exponential function presented in these didactic materials from the perspective of the Theory on Semiotics Representations Registers in terms of congruence and non-congruence phenomena?” The development of this bibliographic qualitative research pointed to the mobilization, manipulation and coordination of semiotic representations of the exponential function found in didactic materials, in which they enable the understanding of mathematical objects, through different representations, providing the teacher with differentiated learning situations.
Phenomenon of congruence and non-congruence about an exponential function in teaching materials
Keywords: Função exponencial; Registro de representação semiótica; Fenômeno de congruência e não congruência; Caderno do professor; Livro didático; Exponential function; Registration of semiotic representation; Phenomenon of congruence and non-congruence; Teacher's notebook; CIENCIAS EXATAS E DA TERRA::MATEMATICA